CAFFEINE ISOLATION AND CYTOTOXIC ACTIVITY OF CHLOROFORM FRACTION FROM ETHANOL EXTRACT OF DURIOKUTEJENSIS AGAINST T47D CELL LINE - Amaliyah Dina Anggraeni, AghniaFuadatul Inayah, Haryoto, (Chelonian Research Foundation, 2024)
Background and Aims: Approximately 19 of 28 species of durian were grown in Borneo. One of them, Duriokutejensis (durian pulu) have not been explored for its potential in anti-cancer treatments. This study aimed to isolate chemical compounds and to evaluate the cytotoxicity of the crude extract and isolated compounds from the chloroform fraction of durian pulu’s stem bark against breast cancer T47D cell line. Methods: The extracts were screened for phytochemicals such as flavonoid, terpenoid, alkaloid, saponin, tannin, polyphenol, and anthraquinone. The vacuum liquid chromatography (VLC) technique was employed to extract fractionation. Isolation and purification were performed using Sephadex column chromatography. The structure of the pure compound was elucidated by spectroscopic analysis (1H NMR, 13C NMR, COSY, HMBC, and HMQC). The extract and isolated compound were tested against T47D by MTT assay. One compound, caffeine, was isolated from the chloroform fraction. Result: The IC50 values of ethanol extract and caffeine of the stem bark were 331.82 and 361.59 µg/mL, respectively. Conclusion: The findings showed that both the crude extract and its isolated compound have no potential of cytotoxic activity against breast cancer T47D cell line. Keywords: Breast Cancer, Caffeine, Cytotoxic, DurioKutejensis, Phytochemical, T47D Cell Line